ADHD and Adolescent Athletes - Nazeer, Ahsan; Mansour, Miriam; Gross, Kathleen A. (Frontiers in Public Health, 2014)
Attention-deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder that affects the child and adolescent population. It is characterized by impairment in attention/concentration, hyperactivity, and impulsivity, all of which can impact performance of athletes. ADHD treatment within the athletic population is a unique challenge. The research in this field has been relatively limited. The National Collegiate Athletic Association and International Olympic Committee both regulate the use of psychostimulants for treatment of ADHD due to their performance-enhancing effects. In this article, authors have discussed the screening methods, pharmacological treatment, side effects, and behavioral approaches for the treatment of ADHD in adolescent athletes.